Ham Petrol ve Benzin Fiyatlarının Sanayi Üretimine Etkisi: MS-VAR Modelleri ile Analizi - (:unkn) unknown (My University, 2015)
Bu makalenin amacı, Türkiye için ham petrol fiyatları ve benzin fiyatlarındaki ani değişimlerin sanayi üretimine etkisinin incelenerek literatüre katkı yapmaktır. Analizler 2005:10-2014:02 dönemi için değişkenlerin doğrusal olmayan özelliklerini yakalamakta başarılı olan Markov Değişim Vektör Otoregresif (MS-VAR) modelleri ile yapılmıştır. LR testi ile analiz döneminde iki rejim olduğu, ham petrol ve benzin fiyatlarındaki değişimin sanayi üretimine etkisinin bu rejimlere bağlı olarak değiştiği bulunmuştur. Ayrıca petrol ve benzin fiyatlarının sanayi üretimine geçiş etkisi olduğu ortaya konulmuştur.

The purpose of this study is contribute to literature by studying the effects of sudden changes both on crude oil import prices and domestic gasoline prices on industrial production for Turkey. Analyses have been done in the period of 2005:10-2014:02 by Markov-switching vector autoregressive (MS-VAR) models which are successful to capture the nonlinear properties of variables. By using of LR test, it has been found that there are 2 regimes in the analysis period and it has been found that the effect of the changes of crude oil and domestic gasoline prices on industrial production differs according to these regimes. It has also been demonstrated that there is a passthrough effect from of oil and gas prices to industrial production.
The Effects of Crude Oil Prices and Domestic Gasoline Prices on Industrial Production : MS-VAR Analysis
Keywords: İktisat; İşletme